An annual agricultural production statistics system for Uganda: Design considerations - Muwanga-Zake, E. S. K. (International Food Policy Research Institute, 2009)
The main objective of agricultural statistics is to provide information on agricultural production. The data collected include the range and quantity of crops and livestock produced; the amount of land put to crop or livestock production; how the agricultural production is used, whether for own consumption or marketed; the farming systems employed; and the socio-economic conditions of farming households. In Uganda, there are several agencies involved in the collection of various food and agricultural statistics (FAS) led by the Uganda Bureau of Statistics (UBOS) and the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF). However, currently very few agricultural statistics are collected on an annual basis at national and sub-national levels. Among the most important statistics for which there is no regular and current information are crop area, yield, and production. UBOS and MAAIF and their predecessor institutions have never succeeded in putting in place statistical systems to collect annual nationally representative agricultural production data. While attempts have been made in the past - for example, past agriculture censuses were followed with a few annual surveys - subsequently these systems broke down. The focus of this brief is the range of elements that must be addressed in planning for and building a sustainable, effective, and efficient FAS system to produce annual, spatially-disaggregated estimates of agricultural production in Uganda. These design issues include meeting the needs of a wide array of data users, assessing the trade-offs between several data collection and analysis methodologies, institutional arrangements, and ensuring sustained flows of adequate financial resources. Further, the characteristics of the agricultural systems in Uganda makes data collection more difficult due to mixed crop and livestock farming systems, continuous planting and harvesting, use of non-standard units of measure of output, few farmers recording their production, and nomadic pastoral livestock production in some areas, among others.